Penggunaan Mit App Inventor untuk Aplikasi Hitung Kalori dari Langkah Berbasis Android - Endang Ulfa Finarsih; Sularno (GLOBAL SCIENTS PUBLISHER, 2024)
The prevalence of smartphones and their integrated sensors presents an opportunity to develop health-related applications easily accessible to users. This study explores the utilization of MIT App Inventor, a user-friendly platform, to create a mobile application for calculating calorie expenditure based on step counts. The application integrates Android device sensors to accurately track user steps and applies a formula to estimate calorie burn. The development process involves designing a user interface through visual programming, leveraging MIT App Inventor's blocks-based coding paradigm. A usability study was conducted to evaluate the application's functionality and user experience. Results indicate that the application effectively calculates calorie expenditure, providing users with valuable health insights. This research demonstrates the feasibility and accessibility of using MIT App Inventor for developing health-oriented applications, catering to the growing demand for personalized health monitoring tools on mobile platforms.